Cooperativismo agropecuario en la posconvertibilidad. Prácticas asociativas y organización institucional de la Unión Agrícola de Avellaneda (2002-2013). - Venturini, Santiago (Universidad Nacional del Litoral, 2020)
The goal of this project is to describe and analyse the cooperative associative practices in the Argentine agricultural sector, especially from the perspective of the new economic growth pattern of post–convertibility. Such practices are analysed from the contributions of the theory of collective action and studies of cooperative institutionalism on the basis of a representative case study of Argentina´s agricultural cooperativism: Unión Agrícola de Avellaneda CooperativaLimitada, in the period 2002–2013. Our hypothesis stands that the entity promotes a macro–cooperative organizational model whose associative practices combine the satisfaction of common material interests and the social capital reproduction of the associated group while ensuring the producers´ individual interests to encourage cooperation. As a result of research, a continuity in the composition of the agricultural cooperative associative practices between the social regime of accumulation of convertibility and the new growth pattern of post–convertibility is recognized